Metallic glasses : thermal, mechanical properties and their correlation - Pang, Jianjun (2012)
To understand the physical factors determining the material properties is of essential importance for the synthesis of new compositions with favorable characteristics. So far the relationship between the electronic structure and the physical properties of metallic glasses (MGs) has not been adequately studied. This project aims to understand and demonstrate the correlation between thermal and mechanical properties of MGs from the viewpoint of valence electron density (VED) in order to provide guidelines for the future design of new systems with desired plasticity. Initially, the thermal and mechanical properties of MGs are explored. A number of MGs were prepared and their amorphous structures were verified by experimental and computational methods. The X-ray diffraction (XRD) and electron diffraction both indicate that there indeed exist short-to-medium-range orders in the amorphous structure. Molecular dynamics simulation confirms the existence of such orders, and also suggests that the amorphous structure consists of diverse polyhedral types, among which some types are dominant (e.g., icosahedral and bcc clusters in Ti50Cu50). These clusters form a five-fold symmetry in the medium range distance. The thermal properties of MGs were studied by continuous differential scanning calorimetry (DSC). For each glassy alloy, the glass transition temperature, and the width of the glass transition region exhibit dependence on heating rate, i.e., they increase with an increase in heating rate; in contrast, the heat enthalpy at crystallization appears to be independent of heating rate, except for the Zr-based sample likely due to its unique crystallization processes. Nevertheless, the larger glass transition temperatures generally correspond to the larger heat enthalpy and the wider glass transition region.